The Preference Size Of Male Mud Crab, Scylla tranquebarica at Success Mating With Female , Scylla olivacea in Controlled Tanks - Gunarto, Gunarto; Sulaeman, Sulaeman; Herlinah, Herlinah (Aquacultura Indonesiana, 2019)
Interspecific hybridization of mud crab Scylla spp has been successfully conducted in controlled tanks. However, there  is no information yet available about the male size  S. tranquebarica is capable to copulate with female of S. olivacea. The objectives of the experiment  is to find out  the  male size of   S. tranquebarica that willingly copulated with newly molted female of  S. olivacea.  Twelve  individual of adolescent female of S. olivacea were reared individually in the conical fibreglass tanks each of  400 L volume. In  another tank,  12 adult male  S. tranquebarica with various size (200-400g/ind.) were also prepared. The crabs fed with chopped trash fish  in the morning (7.00 am) and afternoon (17.00 pm) at 5% of the total crab biomass. Each newly molted female is  transfered to the copulation tank and three male of different size also stocked at the copulation tank, then wait until one of the three male do copulation with female new molt.  The size of copulated crabs (body weight, carapace with, and carapace length) were recorded.  The female crabs sizes were measured  before and after molting, whereas, the  male crab sizes were measured soon after mating process has finished.  Post mating, the female crab then reared individually in the tank until  spawned. The result  showed that male S.tranquebarica  of >300g individual weight are preferable to copulate with female S. olivacea, and contrary none of male crab with size <300g do succsess mating  The time period from mating until  gonad maturity stage IV for the S. olivacea in this study range between 59-103 days.